Quantifying global energy resilience and its carbon reduction effect: The role of technological innovation - Ruquan Lu; Xiaomeng Zhao; Guixian Liu (Energy Strategy Reviews)
By utilizing a global sample of 160 countries from 2000 to 2021, this study first identifies the spatial-temporal characteristics of energy resilience from four dimensions: energy supply resilience, energy consumption resilience, energy security resilience, and energy vulnerability resilience. And its potential effect on carbon emissions (CO2). We find the negative impact of energy resilience on CO2. This study uses the World Bank's classification of income levels of countries globally to categorize the countries within the sample into four groups. The results indicate that the degree of economic growth among the countries and regions directly correlates with how much energy resilience affects CO2. In addition, the mediation analysis reveals the crucial influence of technological innovation on energy resilience affecting CO2. The study provides an essential reference basis for global CO2 reduction and offers new ideas and methods for coping with climate change from the perspective of energy resilience.